One-step in vivo gene knock-out in porcine embryos using recombinant adeno-associated viruses - Gao, Mengyu; He, YuTing; Zhu, XingLong; Peng, WanLiu; Zhou, YanYan; Deng, Yang; Liao, Guangneng; Ni, Wei; Li, Yi; Gao, Jun; Bu, Hong; Yang, Jiayin; et al. (Frontiers in Cell and Developmental Biology, 2024)
Gene-edited pigs have become prominent models for studying human disease mechanisms and gene therapy. CRISPR (clustered regularly interspaced short palindromic repeats) / CRISPR-associated 9(CRISPR/Cas9) technology is widely employed for generating gene-edited pigs. Nevertheless, delivering CRISPR/Cas9 to pre-implantation embryos has traditionally posed challenges due to its reliance on intricate micromanipulation equipment and specialized techniques, resulting in high costs and time-consuming procedures. This study introduces a novel one-step approach for generating genetically modified pigs by transducing CRISPR/Cas9 components into pre-implantation porcine embryos through oviductal injection of recombinant adeno-associated viruses (rAAV). Our study is the first to use rAAV to deliver CRISPR/Cas9 to porcine embryos in vitro as well as in vivo to achieve gene editing and successfully obtain the growth hormone receptor (GHR) gene knockout pigs. This method circumvents the intricate procedures involved in vitro embryo manipulation and embryo transfers, providing a straightforward approach for producing gene-edited pigs and promoting the application of gene-edited pigs in biomedical research.